Photoelectrochemical hydrogen production in water using a layer-by-layer assembly of a Ru dye and Ni catalyst on NiO. Issue 8 (27th May 2016) - Gross, Manuela A.; Creissen, Charles E.; Orchard, Katherine L.; Reisner, Erwin
Abstract : Layer-by-layer assembly of a Ru dye and Ni catalyst on a p-type NiO photocathode enables photoelectrochemical H2 generation in water. Abstract : Capture and conversion of sunlight into the storable energy carrier H2 can be achieved through photoelectrochemical water splitting using light-absorbing cathodes and anodes bearing H2 and O2 evolving catalysts. Here, we report on the development of a dye-sensitised p-type nickel oxide (NiO) photocathode with a hexaphosphonated Ru(2, 2′-bipyridine)3 based dye (RuP3 ) and a tetraphosphonated molecular [Ni(P2 N2 )2 ] 2+ type proton reduction catalyst (NiP ) for the photoreduction of aqueous protons to H2 . A layer-by-layer deposition approach was employed, using Zr 4+ ions to link the phosphonate units inRuP3 andNiP in a supramolecular assembly on the NiO photocathode. This approach keeps the dye in close proximity to the catalyst and semiconductor surface, but spatially separatesNiP from NiO for advantageous electron transfer dynamics. The NiO|RuP3 –Zr 4+ –NiP electrodes generate higher photocurrents and are more stable than photocathodes withRuP3 andNiP co-immobilised on the NiO surface in the absence of Zr 4+ cations linking dye and catalyst. The generation of H2 with the NiO|RuP3 –Zr 4+ –NiP hybrid electrode in pH 3 aqueous electrolyte solution during irradiation with a UV-filtered solar light simulator ( λ > 400 nm, 100 mW cm −2, AM1.5G) has been confirmed by gas chromatography at an underpotential of 300 mV ( E appl = +0.3 V vs. RHE), demonstrating the potential of these electrodes to store solar energy in the chemical bond of H2 .